Validation of high-frequency ultrasound crawling waves sonoelastography - Tecse A. (2020)
Skin diseases cause changes in the elasticity of the skin. Recently, a new ultrasound method which combines crawling waves elastography with a high-frequency ultrasound (HF-US) system was reported for the estimation of skin elasticity. This study applies crawling waves method with an HF-US system in homogeneous and heterogeneous phantoms with similar shear wave speeds found in the literature to validate this technique. In addition, estimation performance was compared between the Phase Derivative (PD) estimator and the Regularized Wave-length Average Velocity Estimator (R-WAVE). Results corroborate the feasibility of this method. Additionally, it suggests that R-WAVE estimator can provide better measurements than PD with a lower coefficient of variation and fewer artifacts. © COPYRIGHT SPIE. Downloading of the abstract is permitted for personal use only.